Elevated Circulating S100A12 Associates with Vascular Disease and Worse Clinical Outcome in Peritoneal Dialysis Patients. Issue 3 (May 2016) - Isoyama, Naohito; Machowska, Anna; Qureshi, Abdul Rashid; Yamamoto, Tae; Anderstam, Björn; Heimburger, Olof; Barany, Peter; Stenvinkel, Peter; Lindholm, Bengt
Background: The pro-inflammatory receptor of advanced glycation end-products (RAGE)-ligand S100A12 is thought to promote, whereas anti-inflammatory soluble RAGE (sRAGE) may protect against, vascular disease. We evaluated circulating S100A12 and sRAGE in relation to vascular disease, inflammation, nutritional status, and mortality risk in peritoneal dialysis (PD) patients. Methods: Plasma S100A12 and sRAGE, biomarkers of inflammation, nutritional status, and comorbidities were analyzed in 82 prevalent PD patients (median age 65 years; 70% men; median vintage 12 months) and, for comparative analysis, also in 190 hemodialysis (HD) patients and 50 control subjects. Associations between mortality risk and concentrations of S100A12 and sRAGE were assessed in PD and HD patients after a mean follow-up period of 31 and 29 months respectively using a competing risk Cox regression model. Results: In PD patients, median S100A12, sRAGE and S100A12/sRAGE were markedly higher than in controls, and S100A12 was 1.9 times higher and median sRAGE 14% lower compared with HD patients. In PD patients, S100A12 associated with C-reactive protein (ρ = 0.46; p < 0.001) and interleukin-6 (ρ = 0.38; p < 0.001), and, negatively, with s-albumin (ρ = -0.27; p < 0.05) whereas sRAGE associated negatively with body mass index (ρ = -0.37; p < 0.001), fat body mass index (ρ = -0.34; p < 0.001), and lean body mass index (ρ = -0.36; p < 0.001). Peripheral vascular disease or cerebrovascular disease (PCVD) was present in 28% of PD patients and, in multivariate analysis, associated mainly with high S100A12 (odds ratio [OR] 3.52, p = 0.04). In both PD and HD patients, the highest versus other tertiles of S100A12 associated with increased mortality. In contrast, sRAGE did not associate with PCVD or mortality in PD and HD patients. Conclusions: Plasma S100A12 and sRAGE are markedly elevated in PD patients. Soluble RAGE was inversely related to body mass indices while S100A12 associated with increased inflammation, PCVD, and mortality, suggesting that S100A12 may identify PD patients at high risk for vascular disease and increased mortality.